The prospect of direct air capture for energy security and climate stability - Shayegh, Soheil (Frontiers in Chemical Engineering, 2023)
Energy policies aim at securing energy supply through domestic production or imports have significant consequences for climate change and its long-term impacts on the economy. Recent European energy crisis as a result of extensive reliance on imported Russian natural gas has highlighted the European Union (EU) energy vulnerability and has challenged its climate change commitments. while switching to alternative domestic fossil fuel sources such as coal in some member states has put the EU climate ambitions in jeopardy, it has also provided new opportunities for upscaling renewable technologies as well as climate stability measures such as direct air capture (DAC). This paper examines the interaction between energy policy and climate stability by considering imported natural gas, domestic coal production, and possible DAC deployment in the EU under two scenarios of full cooperation and full competition among the EU member states. The results suggest that while cooperation induces higher reliance on imported energy, it also provides a strong incentive for DAC uptake. Competition on the other hand, may result in more reliance on domestic coal production and worse climate change outcomes despite the availability of DAC. Therefore, while the EU is striving for a more perfect union, it should consider better alignment of its short-term energy security policies with long-term climate stability ambitions.